(untitled) (KULT_online, 2015)
The anthology expands classical structuralist narratology by exploring two promising paths: transmedial and unnatural narratology. The latter constitutes a relatively new approach in the field. Both these approaches are demonstrated with a broad range of examples and across a scope of different media. The collection of essays thus fruitfully bridges the gap between theory and practice and demonstrates the innovative insights of postclassical narratology.